Improving Students’ Mastery of Arabic Vocabulary Through Make-a-Match Type Cooperative Learning - Mustofa, Ady Muh. Zainul; Arsita, Elsa (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
This study aims to improve students' ability to master Arabic vocabulary by applying the make-a-match type cooperative learning model at MIN 4 Sarolangun. The research method used was Classroom Action Research (PTK) involving 31 fifth-grade students as research subjects. Data was collected through observation, interviews, tests and documentation. The results showed that applying the make a match cooperative learning model effectively increased students' ability to master Arabic vocabulary. Students experience improvement in expanding vocabulary, understanding the meaning of words in Arabic, and improving speaking and listening skills. In the learning process, students can help each other understand Arabic concepts and feel more confident. Arabic teachers should consider applying this learning model to improve Arabic learning at school. The results of this study provide an important contribution related to learning Arabic and can be a reference for the development of innovative learning methods in the future.